Treatment of posterior dislocation following surgical ante-version overcorrection with de-rotation osteotomy of proximal femur in a child with developmental dysplasia. Importance of operative planning: a case report - Nanaiah, Pawan B. (International Journal of Contemporary Pediatrics, 2026)
Proximal femoral osteotomy is commonly performed as an adjunct to open reduction in developmental dysplasia of the hip (DDH) in children presenting after walking age. Inadequate operative planning or incorrect execution of bony procedures can lead to instability and redislocation, resulting in significant morbidity. We report a 7-year-old boy with bilateral DDH who presented with painless limp following two previous surgeries performed elsewhere. The right hip developed posterior dislocation following excessive derotation during proximal femoral osteotomy, while the left hip remained stable. Clinical examination and radiographs demonstrated posterior instability of the right hip with acetabular dysplasia and rotational malalignment of the proximal femur. Revision surgery was planned with extensive soft tissue release, correction of femoral retroversion through rotational osteotomy, and Dega pelvic osteotomy to address posterior and lateral acetabular deficiency. The hip was stabilized with capsulorrhaphy and temporary trans-articular Kirschner wire fixation followed by spica immobilization. At 18 months of follow-up, the hip remained stable with satisfactory remodeling of the acetabulum and proximal femur, and no evidence of avascular necrosis. Excessive derotation during femoral osteotomy can result in femoral retroversion and posterior hip dislocation. Accurate intraoperative assessment of femoral version and adherence to a structured surgical protocol are essential to prevent such complications in DDH surgery.